Developing The Sehati Model Through Experiential Learning and Aji Saka 3D Animation for Early Childhood Social-Emotional Development - Titis Antika Sari; Sri Utaminingsih; Edris Zamroni (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aimed to analyze learning needs, develop the SEHATI model, and evaluate its potential to improve early childhood social-emotional development across different cognitive styles. The study employed a R & D approach adapted from Borg and Gall, consisting of six stages: needs analysis, planning, product development, preliminary testing, revision, and field testing. Participants were 45 children from three early childhood education institutions. Data were collected through interviews, observations, questionnaires, and the CEFT to classify field-dependent and field-independent cognitive styles. Data were analyzed using descriptive statistics and a paired-sample t-test. Expert and practitioner validation indicated that the SEHATI model was highly feasible, with an average validity score of 92.2%. Field testing showed an increase in children's social-emotional development scores from 51.3% (pretest) to 78.8% (posttest), with an N-gain score of 0.57 in the moderate category. Children with both field-dependent and field-independent cognitive styles demonstrated positive improvement, although field-dependent children showed slightly higher gains. The paired-sample t-test revealed a significant difference between pretest and posttest scores (p < .05). These findings suggest that the SEHATI model has strong potential to support social-emotional development through experiential learning assisted by Aji Saka 3D animation while accommodating differences in children's cognitive styles.